2021
DOI: 10.1021/acs.inorgchem.1c00124
|View full text |Cite
|
Sign up to set email alerts
|

Maloplatin-B, a Cisplatin-Based BODIPY-Tagged Mito-Specific “Chemo-PDT” Agent Active in Red Light

Abstract: Maloplatin-B, a cisplatin-based complex, namely [Pt­(A-BOD)­(NH3)2]­(NO3) (Pt-A-BOD) with a pendant boron-dipyrromethene (BODIPY) moiety, where HA-BOD is a methyl malonyl chloride derived monostyryl BODIPY ligand, was designed and developed as near-IR light (600–720 nm) organelle-targeting photodynamic therapy agent. The complex [Pt­(acac)­(NH3)2]­(NO3) (Pt-Ac) was used as a control. Pt-A-BOD displayed an absorption band at 616 nm (ε = 2.9 × 104 M–1 cm–1) in 10% dimethyl sulfoxide/Dulbecco’s Modified Eagle’s M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 65 publications
0
16
0
Order By: Relevance
“…A conjugate 12 based on monoaminostyryl-substituted BODIPY (Scheme 7) was presented by the authors of the article [12]. The conjugate is characterized by absorption bands at 617 nm (ε = 2.9 × 10 4 M −1 cm −1 ) in pH 7.2 10% DMSO/DMEM buffer (v/v).…”
Section: Bodipy Conjugates With Platinum Drugsmentioning
confidence: 99%
See 1 more Smart Citation
“…A conjugate 12 based on monoaminostyryl-substituted BODIPY (Scheme 7) was presented by the authors of the article [12]. The conjugate is characterized by absorption bands at 617 nm (ε = 2.9 × 10 4 M −1 cm −1 ) in pH 7.2 10% DMSO/DMEM buffer (v/v).…”
Section: Bodipy Conjugates With Platinum Drugsmentioning
confidence: 99%
“…This means that complex 12 interacts with DNA through groove binding and/or an intercalative mode. The authors' results of [12] showed that 12 is capable of singlet oxygen generation and exhibits a remarkable PDT effect along with a DNA binding interaction with the possibility of inducing a chemotherapeutic effect.…”
Section: Bodipy Conjugates With Platinum Drugsmentioning
confidence: 99%
“…Organic fluorophores have also found use as effective therapeutic agents harnessing their absorptive properties to give rise to photo-dynamic therapy. For example, a cisplatin-BODIPY conjugate was recently reported which was found to initiate ROS upon irradiation with near-IR light to invoke a cytotoxic response to A549 and HeLa cancer cells [ 286 ]. This conjugate was found to localise within the mitochondria of cells, which is the major cite of ROS production.…”
Section: Imaging Agents Used For Fluorescence Microscopymentioning
confidence: 99%
“…27,28 In addition, the red and green light-active BODIPY-based platinum( ii ) complexes with different molecular designs reported earlier by us had catecholate or other O,O-donor ligands lacking similarity to the present complexes. 29–32 The review article of Guo and co-workers highlights the recent advancements in monofunctional platinum( ii ) chemistry. 33…”
Section: Introductionmentioning
confidence: 99%